Pelas histórias de quem vive: pela escuta de quem conta - Giampaolo, Rafael (Universidade Federal de São Carlos, 2024)
This manuscript presents the Final Course Paper in which an in-depth analysis of the data constructed in the first author's master's research, under the guidance of the second author, was conducted. Thus, this article aims to present the experiences shared by Flora (a fictional name), a participant in the dissertation, as a successful and resistant experience in public school. The object of this research is the daily work of teachers in the basic education system, with the goal of understanding teachers' views on their own work, as well as the demands and roles attributed to them by school management and the community. To achieve this, through qualitative research, we collected data using two main techniques: semi-structured interviews and captioned photos. In this article, we present the data from one participant in light of the discussed references, proposing a reflection on photovoice as a way of producing historical sources, considering the perspective of microhistory and everyday life. We emphasize the potential of these methods as engaged research tools committed to the dialogical process with participants, such as listening, recording, and materializing their stories. Segments of semi-structured interview and photographs produced under the visual photovoice methodology were analyzed. From the considerations, we conclude that photovoice was a powerful tool for recording and materializing unique experiences and narratives about oneself in collectively shared daily routines. In this sense, it was possible to perceive and raise questions for photographic production as a historical source of a micro history of education, whose nuances and subtleties escape the evaluative models based on the performative model that structures what is called "quality" in education.
Through the stories of those who live: by listening to those who tell
Por las historias de quienes viven: por la escucha de quien las cuenta cuenta
Keywords: Photovoice; Fotografia; Professores de educação básica; Terapia ocupacional; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO